Kaposiform lymphangiomatosis: Unifying features of a heterogeneous disorder. Issue 5 (12th October 2014) - Fernandes, Violet M.; Fargo, John H.; Saini, Surbhi; Guerrera, Michael F.; Marcus, Leigh; Luchtman‐Jones, Lori; Adams, Denise; Meier, Emily Riehm
Abstract : Kaposiform lymphangiomatosis (KLA) is a rare proliferation of abnormal lymphatic vessels often complicated by pleural/pericardial effusions and a consumptive coagulopathy that may lead to life threatening hemorrhage. Establishing the diagnosis is challenging due to the clinical heterogeneity and variable findings in laboratory values, radiographic features, and pathologic characteristics. We report three patients who had slowly progressive symptoms and presented with pleural or pericardial effusions, evidence of a consumptive coagulopathy and anemia. Despite being a rare and challenging diagnosis, KLA should be considered in patients presenting with non‐specific indolent symptoms, pleural or pericardial effusions and laboratory evidence of a consumptive coagulopathy. Pediatr Blood Cancer 2015;62:901–904. © 2014 Wiley Periodicals, Inc.